SEEDS OF CHANGE: HEALTH SCIENCE ENTORING PROGRAM FOR UNDERSERVED HIGH SCHOOL STUDENTS. - Ching, Elizabeth (Journal of Cultural Diversity)
In order to have a "diverse workforce," occupational therapy (OT) as a profession must expose and mentor underserved high school students to study in the health sciences. Outreach/exposure, retention/pipeline programming, and mentoring/volunteer experience will be explored to answer the question: "What are the benefits of a health science mentoring program for underserved high school students?" Furthermore, "How can occupational therapy recruit and retain underrepresented racial minority (URM) high school students to the profession ?" This evidence- based paper will describe a cohesive model to expose underserved high school students to occupational therapy. Exposures to health science professions for underrepresented racial minority (URM) high school students was the focus of the literature review. Repeated exposures to health science professions and positive adult encouragement were resources that reinforced the intent to pursue health science professions as a career choice. This evidence-based paper can be used as a basis to start collaboration between a health science university or college and a public high school with underserved students. The health science mentoring program is low-cost provided the university faculty is given release time to perform service to the community. If the occupational therapy faculty member can enlist the cooperation of an additional five health science discipline colleagues, then the exposures to health sciences can accommodate up to 60 high school students rotating through health science stations with an example from a health science university and a public high school health academy.